2011
DOI: 10.1016/j.neuroscience.2011.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial abnormality in sensory, but not motor, axons in paclitaxel-evoked painful peripheral neuropathy in the rat

Abstract: The dose-limiting side effect of the anti-neoplastic agent, paclitaxel, is a chronic distal symmetrical peripheral neuropathy that produces sensory dysfunction (hypoesthesia and neuropathic pain) but little or no distal motor dysfunction. Similar peripheral neuropathies are seen with chemotherapeutics in the vinca alkaloid, platinum-complex, and proteasome inhibitor classes. Studies in rats suggest that the cause is a mitotoxic effect on axonal mitochondria. If so, then the absence of motor dysfunction may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
133
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(153 citation statements)
references
References 45 publications
(91 reference statements)
10
133
0
9
Order By: Relevance
“…Our study revealed swollen disrupted mitochondria in the affected myleinated axons, which coincides with many investigators who suggested that mitochondrial swelling is a characteristic sign in paclitaxel axonopathy [37,38] . This could be explained by affection of Mitochondrial permeability transition pore (mPTP) which is a high conductance channel in mitochondrial inner membrane that contains different proteins including adenine nucleotide translocator (ANT), mitochondrial phosphate carrier (PiC), voltage-dependent anion channel (VDAC), and cyclophilin-D (Cyp-D).…”
Section: Discussionsupporting
confidence: 92%
“…Our study revealed swollen disrupted mitochondria in the affected myleinated axons, which coincides with many investigators who suggested that mitochondrial swelling is a characteristic sign in paclitaxel axonopathy [37,38] . This could be explained by affection of Mitochondrial permeability transition pore (mPTP) which is a high conductance channel in mitochondrial inner membrane that contains different proteins including adenine nucleotide translocator (ANT), mitochondrial phosphate carrier (PiC), voltage-dependent anion channel (VDAC), and cyclophilin-D (Cyp-D).…”
Section: Discussionsupporting
confidence: 92%
“…A similar low-dose regimen (2 mg/kg every other day for a total of 4 doses) also showed distal axonal degeneration, as evidenced by reduced intraepidermal nerve fiber densities and mitochondrial abnormalities [92,93]. Recent studies showed that mitochondria in sensory axons is more susceptible to the toxicity of paclitaxel compared to mitochondria in motor axons, providing a potential hypothesis as to fiber selectivity of paclitaxel-induced neuropathy [94].…”
Section: Chemotherapy-induced Peripheral Neuropathymentioning
confidence: 94%
“…21 Morphological changes such as swollen and vacuolated mitochondria as well as reduced respiration and energy production in axonal mitochondria that results from paclitaxel administration initiates apoptosis pathways by altering intracellular calcium levels. 4,22 Therefore, the neuropathy in this study after low dose paclitaxel administration was due to atypical (swollen and vacuolated) mitochondria in peripheral sensory axons, both C-fibers and myelinated axons as well as the loss of intraepidermal nerve fibres. Both agents may have acted centrally to produce analgesic synergism.…”
Section: Discussionmentioning
confidence: 77%
“…Evidence of swollen and vacuolated mitochondria in peripheral sensory axons, both C-fibers and myelinated axons has been reported. 4 Its use is limited by Myelossupression and peripheral neurotoxicity. 3 Clinically, the sensory neurotoxicity produced by paclitaxel include allodynia, numbness, tingling, and burning pain which often begin symmetrically in the feet and sometimes appear simultaneously in both hands and feet.…”
Section: Introductionmentioning
confidence: 99%